Pengaruh Motivasi Kerja, Beban Kerja, dan Audit MSDM terhadap Kinerja Karyawan pada Perawat Rumah Sakit Harapan Magelang - Nurmala, Ahya; Hartono, Budi; Novitaningtyas, Ivo (IPB University, 2024)
Employee performance is one of the key factor in determining the success of an organization or company. Employee performance is influenced by several aspects, including work motivation, workload, and human resource management (HRM) audits. This study aims to determine the influence of work motivation, workload, and HRM audits on the performance of nurses at Harapan Hospital Magelang. This study employs a quantitative method with a causal associative approach. Data analysis conducted using descriptive statistical analysis, validity and reliability tests, classical assumption tests, multiple linear regression analysis with a significance level of 0.05, hypothesis testing, and model feasibility testing using SPSS version 26. The results of this study demonstrate that the variable of work motivation has a positive and significant effect on nurse performance, with a ?????? value of 5.144, which is greater than the ?????? value of 1.983 and a significance value of 0.000, which is less than 0.05. Additionally, the study proves that the workload variable also has a positive and significant effect on nurse performance, with ?????? of 5.438 greater than thecritical ?????? value of 1.983 and a significance value of 0.000, which is less than 0.05. However, in this study, the HRM audit variable does not have influence on nurse performance, with the ?????? value-1.968, which is greater than the ?????? value -1.983 and a significance value of 0.052, which is greater than 0.05.